Penman-Monteith with missing data and Hargreaves-Samani for ETo estimation in Espírito Santo state, Brazil - Luan P. Venancio; Fernando F. da Cunha; Everardo C. Mantovani; Gilberto C. Sediyama; Fernando C. Eugenio; Catariny C. Aleman (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The Penman-Monteith method (PM-FAO) is recommended as standard for calculation of reference evapotranspiration (ETo). However, its use requires a series of meteorological variables that is not normally available, restricting its application in many locations. A solution to the problem of unavailability of meteorological data was presented in FAO Bulletin 56, which contains methodologies for estimating wind speed, solar radiation and relative humidity. The objective of the present study was to evaluate the performance of the PM-FAO methodologies for missing data and Hargreaves-Samani as alternatives to the PM-FAO standard method at different time scales and seasons for the municipalities of Linhares and São Mateus, located in the northern region of the state of Espírito Santo. The comparison was performed using linear regression parameters (β0 and β1), coefficient of determination, standard error of estimation (SEE) and coefficient of performance. The best alternative to the standard PM-FAO standard method for estimating ETo in the studied area was the Penman-Monteith method with missing wind speed data, since the R2 for this method always remained above 0.94 and the confidence coefficient was classified as great, for all seasons and scales. The Hargreaves-Samani method did not present satisfactory performance, with R2 below 0.7, regardless of the time scale and time of the year, and it yielded the greatest SEE (1.0 mm d-1) at spring on a two-day scale. Thus, its use in the northern region of the Espírito Santo state is not recommended.